Hemorrhagic schwannoma of the trochlear nerve: Case report and a review of the literature - Lei, Jin; Li, Yu; Wan, Xueyan; Wang, Junwen; You, Chao; Zhao, Kai; Niu, Hongquan (Frontiers in Oncology, 2023)
Background: Schwannomas of the trochlear nerve with the absence of systemic neurofibromatosis are considerably uncommon, especially complicated by intra-tumoral hemorrhage. Due to the lack of typical clinical manifestations and imaging findings, a definite diagnosis of trochlear schwannomas before surgery is particularly difficult. Case presentation: We report the case of a 64-year-old female patient who presented with a unilaterally intermittent headache of 2 months’ duration and without a remarkable neurological deficit at admission. Imaging studies revealed a well-demarcated cystic-solid lesion with mixed signal beside the brainstem and suprasellar cisterna. The patient underwent a surgical operation with total resection of the tumor by a subtemporal surgical approach. The tumor was intraoperatively found to originate from the trochlear nerve and was pathologically confirmed as a hemorrhagic schwannoma with cystic degeneration. Conclusions: We describe this case in detail and conduct a concomitant survey of the literature, summarizing the clinical presentations, radiological features, surgical treatment, and the possible mechanisms of hemorrhage in relevance to trochlear nerve schwannoma.